Spirit of place artists, writers & the British landscape - Owens, Susan 19XX- (Thames & Hudson, 2020)
When we look at the landscape, what do we see? Do we experience the view over a valley or dappled sunlight on a path in the same way as those who were there before us? We have altered the countryside in innumerable ways over the last thousand years, and never more so than in the last hundred. How are these changes reflected in - and affected by - art and literature? English landscape painting is often said to be an 18th-century invention. But when we look for representations of the countryside in British art and literature, we find a story that begins with Old English poetry and treads a winding path up to the present day. Spirit of Place offers a panoramic view of the British landscape as seen through the eyes of writers and artists from Bede and the Gawain-poet to Gainsborough, Austen, Turner and Constable; from Paul Nash and Barbara Hepworth to Robert Macfarlane. Guided by these distinctive voices and imagery, and with a sharp eye for an anecdote, Susan Owens elucidates how the British landscape has been framed, reimagined and reshaped by generations. Each account, whether limned in a psalter, jotted down in a journal or constructed from sticks and stones, holds up a mirror to its maker and their world
Includes bibliographical references and index
Keywords: Geschichte; Kunst; Literatur; Landschaft -- Motiv; Landschaftsmalerei; Großbritannien; English literature / History and criticism; Landscapes in literature; English literature; Criticism, interpretation, etc